Simulation Study of Cutting Tool System Using Intelligent Active Force Control - M. M., Hatifi; M. F., Hassan; A. R., Yusoff (Faculty Mechanical Engineering, UMP, 2011)
This paper presents a study of vibration control through an active force control (AFC) scheme. AFCs are used widely in dynamic system control and are highly robust control schemes, although under unknown disturbances and operation conditions. In this study, the AFC was incorporated with a conventional proportional-integral-derivative (PID) controller to control an active vibration isolation system. A cutting tool of a turning machine with two degrees of freedom is used in this study. A harmonic force due to an unbalanced rotating mass and a sinusoidal response that represented an internal disturbance were applied to both axes (X and Y) of the models, respectively. Generally, the estimated mass (EM) is the most significant parameter in an AFC scheme; thus, the interest in this study was to obtain the EM via a conventional crude approximation method and an intelligent fuzzy logic method. A new AFC scheme with fuzzy logic control (FLC) was proposed (AFCFLC), which is an AFC combined with a PID and FLC. The main purpose of this scheme was to obtain the optimum EM value via the intelligent method and to suppress vibration. Finally, a demonstration of a comparison study between each control scheme was carried out, which revealed clearly that the proposed AFCFLC scheme was the most superior control method for vibration isolation in both axes of the cutting tool models.